Pelaksanaan Pembagian Harta Warisan Di Desa Tuntungan II Kecamatan Pancur Batu Kabupaten Deli Serdang Menurut Hukum Adat - Dari, Nayu Triska Wulan; Rani, Diana (Wajah Hukum, 2023)
This inheritance law cannot be separated from human life itself because this inheritance law is very closely related between parents and children in terms of property that will be owned or given by their children. Therefore, related to the problem of heirs, they should know about who is called an heir, then the rights and obligations that must be accepted by heirs and the grouping of heirs in inheritance law so as to reduce the existence of misunderstandings between heirs with one another in distribution of inheritance in society. In the distribution of inheritance on inheritance in general, it must be fairly regulated based on the law that applies in the inheritance process. Therefore, the distribution of inherited assets should fulfill the elements of justice and achieve peace in the distribution of inherited assets because it is the most important thing so as not to cause legal consequences in the future. The research method is empirical legal research type, library data sources and field research. The sampling technique is used by purposive sampling. Data collection techniques are interviews and library research as well as qualitative analysis. The results of the research are the implementation of the distribution of inheritance in Tuntungan II Village, Pancur Batu District, Deli Serdang Regency according to customary law, the karo village community still uses two applicable laws, namely the national law (KUHPerdata) and customary law where the customary law prioritizes the distribution to male heirs rather than female heirs and the obstacles faced in implementing the distribution of inheritance in Tuntungan II Village, Pancur Batu District, Deli Serdang Regency according to customary law is patrilineal or prioritizing the distribution of heirs to men then raises the greedy nature of male heirs and a sense of unfairness from female heirs, causing disputes / disputes between the two.